Le traitement de l’humour dans les traductions hispanophones d’À la recherche du temps perdu - Thomas Barège (Catalonia)
Translators often stress the difficulty of translating humour, which is generally considered to be specific to a particular culture. In the case of La Recherche, this cultural dimension of humour is compounded by the very specific nature of Proustian humour, which is often subtle and even elitist. The strategies employed by the translators of the six complete translations of La Recherche are manifold, and it will simply be a matter of asking whether Proust is/can be funny in Spanish.